Cape Verde : First Review Under the Policy Support Instrument and Requests for Waivers of Nonobservance and Modification of Assessment Criteria: Staff Report; Supplement; and Press Release. (IMF Staff Country Reports; Country Report ;, 2011)
Cape Verde's economic outlook and policy performance remain favorable. The government should complete implementation of the Public Investment Program (PIP), while reducing external debt. Executive Directors support efforts to rationalize and simplify the tax system and improve tax administration. The tight stance of monetary policy is constraining the growth of private credit to stabilize foreign reserves. The new banking law and finalizing the National Social Security Institute's investment policy guidelines are necessary. Enhancing labor market flexibility will support the government's transformation agenda. Risks to the program remain manageable.